Predator Environment Does Not Predict Life History in the Morphologically Constrained Fish Alfaro cultratus (Cyprinodontiformes: Poeciliidae) - Golden, Kaitlyn B.; Belk, Mark C.; Johnson, Jerald B. (Frontiers in Ecology and Evolution, 2021)
Predation is known to have a significant effect on life history diversification in a variety of species. However, physical constraints of body shape and size can sometimes limit life history divergence. We test this idea in the Costa Rican livebearing fish Alfaro cultratus. Individuals in this species have a narrow body and keeled ventral surface, and females do not develop a distended abdomen when pregnant like other livebearing fishes. Here, we describe the life history of A. cultratus from 20 different populations across both predator and non-predator environments. We found significantly lower reproductive allotment in females from predator environments than in females from non-predator environments, but no significant difference in female or male size at maturity, number of offspring produced by females, or size of offspring. We found that A. cultratus exhibit isometric patterns of allocation for clutch dry mass in relation to female dry mass in predator and non-predator environments. Our results suggest that body shape constraints in this species limit the life history divergence we typically see between populations from predator and non-predator environments in other species.